1975
DOI: 10.1002/jnr.490010510
|View full text |Cite
|
Sign up to set email alerts
|

Regional neurochemical studies on the effect of β,β′ ‐iminodipropionitrile (IDPN) in the rat

Abstract: A permanent hyperkinetic syndrome, characterized by excitation, choreiform head and neck movements and circling, which has led to it being called collectively the "ECC-syndrome," is induced in rats by the daily IP administration of beta, beta'-iminodipropionitrile (IDPN), 300 mg/kg, for 7 days. The levels of the biogenic amines, norepinephrine (NE), dopamine (DA), serotonin (5-HT) and its metabolite 5-hydroxyindoleacetic acid (5-HIAA), were measured in the striatum, midbrain, medulla, cortex, and cerebellum on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

1977
1977
2014
2014

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…These abnormalities bear some resemblance to the phenomena observed after acute injection of dopamine (DA) (Lewander, 1977) and serotonergic agonists (Green, 1984). The persistent changes seen after IDPN treatment can be blocked by drugs that are inhibitory to both the dopamine (Cadet et al, 1987b;Diamond et al, 1982b;Langlais et al, 1975;Schneider, 1984) and the norepinephrine system (Cadet et al, 1987a).…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…These abnormalities bear some resemblance to the phenomena observed after acute injection of dopamine (DA) (Lewander, 1977) and serotonergic agonists (Green, 1984). The persistent changes seen after IDPN treatment can be blocked by drugs that are inhibitory to both the dopamine (Cadet et al, 1987b;Diamond et al, 1982b;Langlais et al, 1975;Schneider, 1984) and the norepinephrine system (Cadet et al, 1987a).…”
Section: Introductionmentioning
confidence: 88%
“…Very few studies have been carried out on the possible biochemical changes that may be associated with the IDPN-induced syndrome. In rats, it was reported that both serotonin (5-HT) and norepinephrine (NE) levels were increased on the day that the syndrome developed (7th day of injection); but while the level of NE returned to normal 1 week after the last injection of IDPN, that of 5-HT was significantly reduced at that time (Langlais et al, 1975). There was no change reported in the concentration of DA in the rat (Langlais et al, 1975) or mice brain (Gianutsos and Suzdak, 1985).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the brain, IDPN has been shown to increase glial fibrillary acidic protein (GFAP) expression in the cingulate cortex and hippocampus (Seoane et al, 1999). There also are studies to show neurochemical or oxidative stress-related effects in the brain by IDPN exposure (Langlais et al, 1975;Gianutsos and Suzdak, 1985;Perumal et al, 1991). IDPN also causes a loss of hearing and vestibular function acutely by hair cell degeneration (Crofton et al, 1994;Llorens and Demêmes, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these studies, the biochemical basis for this syndrome remains unknown. One study reported decreased levels of serotonin (5-HT) and its metabolite, 5-hydroxyindolacetic acid (5-HIAA), in the midbrain and striatum of rat brain 1 week after the appearance of the syndrome (Langlais et al, 1975). Although experimentally induced reductions in brain 5-HT have been associated with increased locomotor activity and a variety of behavioral disturbances, the delay (7 days) between the appearance of the syndrome and the reductions in 5-HT and 5-HIAA levels cast some doubt on the direct involvement of serotonergic systems in the production of the "ECC-Syndrome.…”
Section: Introductionmentioning
confidence: 99%